2002
DOI: 10.1002/mar.10023
|View full text |Cite
|
Sign up to set email alerts
|

“So that's what that is”: Examining the impact of analogy on consumers' knowledge development for really new products

Abstract: The ever-accelerating pace of technological change has heralded an increasing number of new product introductions involving products that defy classification within existing categories. With the advent of these so-called "really new products," new questions about the influence of prior knowledge on consumer learning emerge. Chief among these is whether and to what extent prior knowledge plays a role in the comprehension of such products. Applying analogical learning theory to address this question, this invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 41 publications
3
76
0
1
Order By: Relevance
“…In line with the literature in this area, and as with perceptions, familiarity with ICT appeared to influence the willingness to accept technological interventions in community care (Brown and Venkatesh 2005;Gregan-Paxtan et al 2002;Moreau et al 2001). It is unsurprising, therefore, that the younger participants,, who reported the highest rates of technical proficiency, valued technologies that had a more technically complicated means of intervention.…”
Section: Discussionsupporting
confidence: 59%
“…In line with the literature in this area, and as with perceptions, familiarity with ICT appeared to influence the willingness to accept technological interventions in community care (Brown and Venkatesh 2005;Gregan-Paxtan et al 2002;Moreau et al 2001). It is unsurprising, therefore, that the younger participants,, who reported the highest rates of technical proficiency, valued technologies that had a more technically complicated means of intervention.…”
Section: Discussionsupporting
confidence: 59%
“…Previous research showed that communicating analogies of a new product to something known increases product comprehension (Feiereisen, Wong, & Broderick, 2008;Gregan-Paxton, Hibbard, Brunel, & Azar, 2002). Based on this, we predicted that communicating similarity of a complex novel product with a comparable familiar product would increase coping potential and interest in the product.…”
Section: Experiments 1: Similarity To a Familiar Productmentioning
confidence: 88%
“…Previous studies have explored the idea that consumer evaluations of a new product could be manipulated by reminding consumers of a similar example to enhance the corresponding product attributes with the analogy process (Goode, Dahl, & Moreau, 2010;Gregan-Paxton & Roedder, 1997;Gregan-Paxton et al, 2002). Therefore, the present research approaches the issue of consumer evaluations of brand extension from the perspective of case-based reminding and suggests that the proposed brand extension evaluations can be manipulated by reminding consumers of a similar brand in the extension category.…”
Section: Analogical Reasoning and Case-based Remindingmentioning
confidence: 91%